Hubungan di antara faktor kepuasan komunikasi dan komitmen terhadap organisasi di kalangan kakitangan agensi penguatkuasaan undang-undang di Malaysia - Redzaime, Abd Hamid (2018)
The main purpose of this study was to establish the relationship between communication satisfaction and organizational commitment among workers. In addition, this study has chosen five main elements in order to measure their effects on the organizational commitment. The main instrument that was used in this study was the utilization of a questionnaire which was developed using the models that have been selected by the researcher. They were Communication Satisfactional Questionaires (CSQ) by Down and Hazen (1990) and Organizational Commitment Questionaires (OCQ) by Allen dan Meyer, (1997). A total of 152 repondents have participated in this study and they were all from a selected law enforcement agency in Malaysia. From the results gathered, the researcher has come to conclusion that there are significant relationship between communication satisfaction and organizational commitment. This has led to the conclusion that the level of communication satisfaction level in the organization is low which has led to a relatively low level of organizational commitment. Among the five (5) elements that have been chosen by the researcher in which have been tested through Multiple Linear Regression procedure, it was identified that all five elements have a significant relationship with Organizational Commitment. Corporate Perspective, Supervisory Communication, Horizontal Communication dan Organizational Integration respectively play a big role in determining the level of employee commitment towards the organization.